Cholesterol binding to ion channels - Levitan, Irena; Singh, Dev K.; Rosenhouse-Dantsker, Avia (Frontiers in Physiology, 2014)
Numerous studies demonstrated that membrane cholesterol is a major regulator of ion channel function. The goal of this review is to discuss significant advances that have been recently achieved in elucidating the mechanisms responsible for cholesterol regulation of ion channels. The first major insight that comes from growing number of studies that based on the sterol specificity of cholesterol effects, show that several types of ion channels (nAChR, Kir, BK, TRPV) are regulated by specific sterol-protein interactions. This conclusion is supported by demonstrating direct saturable binding of cholesterol to a bacterial Kir channel. The second major advance in the field is the identification of putative cholesterol binding sites in several types of ion channels. These include sites at locations associated with the well-known cholesterol binding motif CRAC and its reversed form CARC in nAChR, BK, and TRPV, as well as novel cholesterol binding regions in Kir channels. Notably, in the majority of these channels, cholesterol is suggested to interact mainly with hydrophobic residues in non-annular regions of the channels being embedded in between transmembrane protein helices. We also discuss how identification of putative cholesterol binding sites is an essential step to understand the mechanistic basis of cholesterol-induced channel regulation. Clearly, however, these are only the first few steps in obtaining a general understanding of cholesterol-ion channels interactions and their roles in cellular and organ functions.